Airway wall splice quantitative trait locus analysis reveals novel downstream mechanisms for known asthma single-nucleotide polymorphisms. Issue 2 (3rd April 2023) - Kole, Tessa M.; Pouwels, Simon D.; Bults, Rene; Ketelaar, Marlies E.; Guryev, Victor; Koll, Lisanne; Kerstjens, Huib A.M.; Nawijn, Martijn C.; Faiz, Alen; van den Berge, Maarten
Genome-wide association studies (GWAS) [1] have identified single-nucleotide polymorphisms (SNPs) associated with the presence of asthma. It is notoriously difficult to link identified SNPs to downstream functional effects leading to increased asthma risk. A possible strategy to do this is to perform expression quantitative trait locus (eQTL) analyses, which pinpoint the direct effects of SNPs on mRNA expression levels. However, eQTL analyses merely focus on the expression level and do not consider alternative splicing. Alternative splicing is a naturally occurring process in which RNA can be spliced into multiple different transcripts, leading to different forms of a protein, which can strongly affect its function [2]. The present study aimed to identify the effect of asthma-related SNPs on alternative splicing of genes expressed specifically in the airway wall, the predominant site where the inflammatory process occurs. We hypothesised that this might reveal novel downstream mechanisms linking previously identified GWAS SNPs to asthma. Studying the effects of asthma SNPs on alternative splicing can lead to new insights into asthma pathophysiology. More specifically, a 17q12 SNP is associated to alternative splicing of GSDMB . https://bit.ly/3W49oTs